Functional appliances - Sukhpal Kaur; Sanjeev Soni; Anil Prashar; Naveen Bansal; Jaskaran Singh Brar; Maninderdeep Kaur (Wolters Kluwer Medknow Publications, 2017)
The purpose of this review is to evaluate the previous studies that describe the effects of functional appliances and their efficiency in treating class II malocclusion. This review is limited to three appliances: activator, bionator, and twin-block appliances.